2015
DOI: 10.3389/fmars.2015.00067
|View full text |Cite
|
Sign up to set email alerts
|

Conservation benefits of an interdisciplinary approach to marine mammal science

Abstract: Protected resource economists can greatly enhance the science and conservation of marine mammals, however such contributions are often hampered by a lack of understanding of the role of natural resource economics on behalf of more traditional marine mammal scientists. The three major threats to marine mammals-fishery bycatch, increasing underwater sound, and climate change could be more effectively addressed with an interdisciplinary approach that includes the full valuation of costs and benefits to society. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…To better understand how we can achieve such complex integration of variables, more research and data are needed (Broderick, 2015;Buhl-Mortensen et al, 2015;Hilário et al, 2015), in addition to cross-disciplinary collaborations that will improve the quantity and quality of information available for decision-making (Lent, 2015;Bisack and Magnusson, 2016). A promising endeavor in that vein is the Ecological Marine Units (EMUs) project (Sayre et al, 2017), which offers a baseline three-dimensional global map of marine ecosystems.…”
Section: Data Selection and Fitness For Usementioning
confidence: 99%
“…To better understand how we can achieve such complex integration of variables, more research and data are needed (Broderick, 2015;Buhl-Mortensen et al, 2015;Hilário et al, 2015), in addition to cross-disciplinary collaborations that will improve the quantity and quality of information available for decision-making (Lent, 2015;Bisack and Magnusson, 2016). A promising endeavor in that vein is the Ecological Marine Units (EMUs) project (Sayre et al, 2017), which offers a baseline three-dimensional global map of marine ecosystems.…”
Section: Data Selection and Fitness For Usementioning
confidence: 99%
“…Given today's growing range of threats that far surpass mortality from direct hunts, the IWC now has a much broader range of issues and stakeholders (Wright et al, 2016). The emerging threats to whales are externalities from sectors that are not part of the regular IWC stakeholder groups: fishing; underwater drilling and extraction; shipping noise and emissions, and other ocean pollution (plastics) (Lent, 2015). These externalities are rarely if ever internalized into production and consumption decisions, although regulatory processes might require impact analyses on marine mammals.…”
Section: Case Study 3: International Whaling Commissionmentioning
confidence: 99%
“…Market-based instruments also include taxes that incentivize environmentally desirable behavior (e.g., a bycatch tax) and risk pools that provide a means for sharing the risk of unintended impacts on MPR across resource users (Holland and Jannot, 2012). Lent (2015) and others have advocated for market-based instruments to help address the major threats facing marine mammals. Further, empirical analyses have found that market mechanisms can foster efficient outcomes for MPR and associated stakeholders.…”
Section: Economic Tools For Mpr Managementmentioning
confidence: 99%